JANNS.co / Alifah Ilyana Mohd Rafi … [et al.] - Mohd Rafi, Alifah Ilyana; Laser, Jassinta; Mohd Fadzilla, Nur Syahira; Ramli, Nurul Akma An Najwa; Mohd Adaha, Siti Sarah (2022)
JANNS.co is a company where the main areas of business are in device and technology. In the context of the postmodernist era, the globe is overshadowed by data and communication technology. Advances in technology have bribed new lifestyles in addition to dynamic consumer tastes. Technology has taken this world on a pervasive basis. Nearly every second society can use technology by dominant every factor at their fingertips. This case has become important to the community as a result of its replacement agenda that encompasses a place within the hearts of the community. This can be so because information technology was created to please our busy lives. Our current cyber world has been born to the current generation of IT literate. Indeed, if thought about prudently, the sophistication of technology brings edges to our society and country. Therefore, our vision is to be the most advanced company in technology and to offer greater mobility and convenience. Furthermore, our missions are: